The role of requirements engineering in the development of multi-agent systems - Prado Leite, Julio César Sampaio do (2005)
There has been an increasing number of literature dealing with the software engineering aspect of building “agent oriented software”. In principle, agent oriented software is software implemented in platforms in which software pieces behave with a certain level of independence from other software pieces. An important characteristic of agent oriented software is the level of intelligence available for each software piece, or agent. (Párrafo extraído del texto a modo de resumen)